Molecular docking studies of YKT tripeptide and drug delivery system with poly(ε-caprolactone) nanoparticles - Bicak, Bilge; Kecel-Gunduz, Serda; Budama-Kilinc, Yasemin; Ozdemir, Burak (WILEY-V C H VERLAG GMBH, 2022)
Tyrosyllysylthreonine (YKT) is a peptide structure that contains three different amino acids in its structure and has anticancer properties. The main purpose of this study is to reveal the structural interactions of the peptide and to increase the efficiency of the peptide with nanoformulation. For these purposes, YKT-loaded poly(epsilon-caprolactone) (PCL) nanoparticles (NPs) were synthesized using the double-emission precipitation method and the obtained NPs were characterized with a Zeta Sizer, UV-Vis, Fourier transform infrared-attenuated total reflection spectrometers, scanning electron microscopy, and transmission electron microscopy. The in vitro release profile of the peptide-loaded PCL NPs was determined. In molecular modeling studies, PCL, PCL-polyvinyl alcohol (PVA), and PCL-PVA-YKT systems were simulated in an aqueous medium by molecular dynamics simulations, separately. The information about the interactions between the YKT tripeptide and the epidermal growth factor and androgen, estrogen, and progesterone receptors were obtained with the molecular docking study. Additionally, the ADME profile of YKT was determined as a result of each docking study. In conclusion, tripeptide-based nanodrug development studies of the YKT tripeptide are presented in this study.
Keywords: molecular docking; molecular modeling; nanoparticle synthesis; peptide; poly(epsilon-caprolactone); CAPROLACTONE NANOPARTICLES; IN-VITRO; CONTROLLED-RELEASE; ACCURATE DOCKING; LUNG-CANCER; POLYCAPROLACTONE; PROTEIN; DETERMINANTS; OPTIMIZATION; RECEPTORS; Pharmacology & Pharmacy; Chemistry